Impact of wars and natural disasters on emerging and re-emerging infectious diseases - Topluoglu, Seher; Taylan-Ozkan, Aysegul; Alp, Emine (Frontiers in Public Health, 2023)
Emerging Infectious Diseases (EIDs) and Re-Emerging Infectious Diseases (REIDs) constitutes significant health problems and becoming of major importance. Up to 75% of the EIDs and REIDs have zoonotic origin. Several factors such as destruction of natural habitats which leads humans and animals to live in close proximity, ecological changes due to natural disasters, population migration resulted from war or conflict, interruption or decrease in disease prevention programs; insufficient vector control applications and sanitation are involved in disease emergence and distribution. War and natural disasters have great impact on the emergence/re-emergence of the diseases in the population. According to World Bank estimation, 2 billion people are living under poverty and fragility situations. Wars destroy the health systems and infrastructure, curtail the existing disease control programs and cause population movement leading increase in exposure to health risks and favor emergence of infectious diseases. A total of 432 catastrophic cases associated with natural disasters were recorded globally in 2021. Natural disasters increase the risk of EIDs and REIDs outbreaks by damaging the infrastructure and leading displacement of populations. A Generic National Action Plan covering risk assessment, mechanism for action, determination of roles and responsibilities of each sector, establishment of a coordination mechanism etc. should be developed.